2015
DOI: 10.1016/j.jconrel.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface chemistry on nanoparticle interaction with gastrointestinal mucus and distribution in the gastrointestinal tract following oral and rectal administration in the mouse

Abstract: It is believed that mucoadhesive surface properties on particles delivered to the gastrointestinal (GI) tract improve oral absorption or local targeting of various difficult-to-deliver drug classes. To test the effect of nanoparticle mucoadhesion on distribution of nanoparticles in the GI tract, we orally and rectally administered nano- and microparticles that we confirmed possessed surfaces that were either strongly mucoadhesive or non-mucoadhesive. We found that mucoadhesive particles (MAP) aggregated in muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
234
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(241 citation statements)
references
References 68 publications
5
234
0
Order By: Relevance
“…However, drugs or drug-loaded nanoparticles must pass through the “filter” formed by highly viscoelastic and adhesive layers of mucus coating the GI tract epithelium, or be trapped and rapidly cleared along with the ‘sloppy’ layers of mucus farthest from the epithelium [9, 10]. We previously found that nanoparticles sufficiently small and well-coated to slip through the mucus barrier, mucus-penetrating particles (MPP), can be efficiently delivered to the entire colorectal epithelial surface [11-14]. Rapid and widespread distribution of MPP was driven by the rapid absorption of water from hypotonic solution “advectively” transporting MPP to the epithelium much faster than by diffusion alone [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, drugs or drug-loaded nanoparticles must pass through the “filter” formed by highly viscoelastic and adhesive layers of mucus coating the GI tract epithelium, or be trapped and rapidly cleared along with the ‘sloppy’ layers of mucus farthest from the epithelium [9, 10]. We previously found that nanoparticles sufficiently small and well-coated to slip through the mucus barrier, mucus-penetrating particles (MPP), can be efficiently delivered to the entire colorectal epithelial surface [11-14]. Rapid and widespread distribution of MPP was driven by the rapid absorption of water from hypotonic solution “advectively” transporting MPP to the epithelium much faster than by diffusion alone [11].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that nanoparticles sufficiently small and well-coated to slip through the mucus barrier, mucus-penetrating particles (MPP), can be efficiently delivered to the entire colorectal epithelial surface [11-14]. Rapid and widespread distribution of MPP was driven by the rapid absorption of water from hypotonic solution “advectively” transporting MPP to the epithelium much faster than by diffusion alone [11]. Similarly, we found that hypotonic vehicles induced fluid absorption by the vaginal epithelium that rapidly delivered water-soluble drugs and MPP to the epithelial surface by advection [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The targeted therapy effect is achieved through preventing the drug release in stomach and triggering release at the target site [8,11]. The specific surface characteristics of nanocarriers can increase the contact between loaded drug and intestinal mucosa and enhance cellular uptake of formulation [3,12,13]. High local drug concentration is created in lesion, resulting in high mortality of cancer cell, which is beneficial to decrease the required dosage and frequency of administration, reduced toxicity and cost [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that mucus-penetrating NPs, characterized by size less than the mucus mesh spacing and non-mucoadhesive surface, preferentially penetrate the mucus layer deeply. In contrast, the mucoadhesive NPs tend to stick to mucus components and aggregate locally [14].…”
Section: Oral Administrationmentioning
confidence: 98%